Analysis Of The Influence Of Work Stress On Employee Performance With Job Satisfaction As An Intervening Variable - Solikhah, Mar’atus (Publikasi Indonesia, 2023)
In this study using a sample of 34 respondents, namely CV. Syntax Corporation Indonesia factory employees. The sample used was a saturated sampling technique. The testing in this study was carried out by analyzing the validity test, reliability test, classic assumption test, path analysis test, determination coefficient (R2),and t test. For partial hypothesis testing, the t test is used, the tcount value obtained for the Job Stress variable (X) for Job Satisfaction (Z) is 3.563 then for the Job Stress variable (X) for Employee Performance (Y) of 2.542 and for Job Satisfaction (Z ) towards Employee Performance (Y) of -1,175. Then based on the results of the Kofisien test of Equation I determination of 0.284 it means that the contribution or work stress relationship is 28.4% and the remaining 71.6%, and from equation II the results are 0.174, meaning that the work stress factor (X) influences job satisfaction (Z) of 17.4%, while the remaining 82.6% is influenced by other factors not included in this study. Then from the results of calculations through Path with the Causal Step method and Product Of Coefficient it is stated that and in this study the results of z calculated are 1.077 and z tables are 0.353. So it can be concluded that z count> z table, the Intervening variable mediates the relationship between the Independent variable and the Dependent variable. Or in other words the Job Satisfaction variable mediates the relationship between the Job Stress variable and the Employee Performance variable.